Analysis and optimization of dry sliding wear characteristics of zirconia reinforced alumina composites formed by conventional sintering using response surface method. (August 2016) - Elsen, S. Renold; Ramesh, T.
Abstract: An experimental investigation of the tribological performance during dry sliding wear was carried out on Zirconia Toughened Alumina (ZTA) ceramic composites. Process parameters for the analysis, such as the amount of Zirconia reinforcement added to alumina matrix, compaction pressure to form the green bodies of required shape and sintering temperature to make the final composite were selected as the control variables. The specific wear rate of ZTA against steel studied using a pin-on-disc method was selected as the response. The tribological experiments were carried out on all the 17 ZTA samples fabricated based on Box-Behnken design. The tribological test parameters such as a constant load of 49.05 N (5 kg) and sliding velocities of 0.3 m/s for a sliding distance of 800 m were kept constant. The regression model was developed for specific wear rate of dry sliding wear and the influential parameters were found to be sintering temperature and weight percentage of Zirconia added to alumina from Analysis of variance (ANOVA). The results concluded that decreasing the amount of Zirconia reinforcement into the alumina matrix and sintering temperature improves the specific wear rate. Also, the High resolution scanning electron microscopy (HR-SEM) analysis was done on the wear tracks to examine the wear mechanism involved. The optimization was done using Response Surface Method and a confirmation test was done to validate the optimized results. Graphical abstract: Highlights: The fabrication of nano crystalline Zirconia Toughened alumina nano composite by pressure less sintering method. Using XRD and TEM the characterization of starting powder and sintered samples were done Using Box Behnken design the 17 experimental runs were developed and the fabrication was done based on the run. The samples were subjected wear test by Pin-On-Disk method and test parameters constant such as load of 49.05 N (5 kg) and sliding velocities of 0.3 m/s for a sliding distance of 800 m The development of regression model for the wear characteristics were done for the fabricated Zirconia Toughened alumina. Using ANOVA the influencing process parameters were identified. HR SEM images of the samples were done to study the wear mechanism of different sintered samples. Finally optimization and confirmation studies were carried out.